WORKLOAD WITH NURSES CARING BEHAVIOR (Correlation studies in IRNA RSUD Kabupaten Jombang) - Achli Arifin; Arif Wijaya; Anin Wijayanti (STIKES Insan Cendekia Medika Jombang, 2012)
Nursing care that is based on caring behavior will contribute to healing and health clients. In practice nurses caring behavior that is applied is still lacking, one contributing factor is the workload is not balanced. The IRNA RSUD Kabupaten Jombang comparison of the number of nurses with clients is 1 : 11, the potential of the heavy workload of nurses and nurse caring behaviors decrease. This study aimed to analyze the relationship between workload with nurses caring behavior in IRNA RSUD Kabupaten Jombang.This research is a cross sectional analytic approach. The population in this study are all nurses who served in a number of 165 nurses IRNA. The sampling technique using a probability sample is done by simple random sampling with specified proportion so large a sample of 62 nurses. Data were collected using a questionnaire which consisted of questionnaires workload and nurses caring behavior.The results showed that the mean value of the workload of nurses is 44.08 and nurses caring behavior is 104.98. Correlation of test results obtained p value of 0.007 (p value <alpha = 0.05). It can be concluded that the average value of the work load approaches the maximum expectation value, the average value of nurses caring behavior approaching the maximum expectation value and significant correlation between workload with nurses caring behavior in IRNA RSUD Kabupaten Jombang. The need for attention to the workload of nurses because the workload will decrease productivity, quality of service, and including the appearance of nurses working in applying caring behavior.